Management of Basic Education and Its Development (A Case Study in MIN 3 Pinang Sori) - Nurul Oktaviana Mekawati; Wandana Simatupang; Fachrul Sanawi; Mesiono Mesiono (STAI Hubbulwathan Duri, 2022)
Management has a central role in organizational structure and culture. This is also the basis for the integrality of management and organization in Islamic educational institutions. This study aims to analyze the management of basic education and its development. The research background is located at MIN 3 Pinang Sori, with a focus on the study of management and development aspects. This research uses a qualitative approach with a descriptive-analytical study method. Phenomenologically, researchers tried to collect data in the field by means of interviews, observations, and documentation. Next, the researcher interprets the data through reduction efforts, data presentation, and verification. Finally, the data is declared valid (valid) if it passes the triangulation test. The results of this study indicate that education management at MIN 3 Pinang Sori is well implemented. This is viewed from the implementation of the institution's vision, mission, and goals through the development of a community-based curriculum (a combination of the madrasa curriculum, national education curriculum, and local wisdom). Then, the strategy used in madrasah development is to improve the quality of academic services and the quality of madrasa graduates. The concrete form is in the form of optimizing extracurricular activities to support the potential of students with academic and non-academic achievements, giving prizes as an appreciation for outstanding students and teachers, increasing human resource competencies based on community needs, training for madrasa human resources, and mediation conducted by the madrasa committee with the local community.